Respuesta :
Answer:
The given quadratic equation [tex]4n^2+28n+49[/tex] factored as [tex](2n+7)^2=(2n+7)(2n+7)[/tex]
Step-by-step explanation:
Given quadratic equation [tex]4n^2+28n+49[/tex]
We have to factorize the given quadratic equation and make the grid of factors.
Consider the given quadratic equation [tex]4n^2+28n+49[/tex]
Using algebraic identity,
[tex](a+b)^2=a^2+2ab+b^2[/tex]
On comparing, we get,
[tex]a^2=4n^2\\\\ \Rightarrow a=2n[/tex]
also, [tex]b^2=49\\\\\Rightarrow b=7[/tex]
Thus, the given quadratic equation [tex]4n^2+28n+49[/tex] factored as [tex](2n+7)^2=(2n+7)(2n+7)[/tex]
The grid is shown in attachment below.
![Ver imagen athleticregina](https://us-static.z-dn.net/files/dc6/6cbcc9fcf2eef69bff0609be67de923d.png)